The biology of green mussel (Perna viridis) cultivated through long line method in mussel farms of Leyte, Leyte, Philippines. - Silaras, Mark Leonard S. (Mark Leonard S. Silaras, 2019)
Perna viridis (green mussel) is a marine bivalve widely cultivated in the Philippines for commercial purposes. Ann assessment on P. viridis cultivated using long line method in Leyte, Leyte was conducted to provide a study on the biological characteristics of mussels in these farms. Three sampling sites were selected to represent the mussel farms in Leyte, Leyte. Mussel samples (n=135) were collected monthly from December 2018 to March 2019. Environmental parameters, phytoplankton biomass and biological parameters were monitored. Specific growth rate shows a general increasing trend in biometric parameters. Meanwhile, there was an increase in phytoplankton biomass in February 2019 (0.20 ug/L) and March 2019 (0.23 ug/L), suggesting food availability for mussels during these months. There was an increase in condition index from December 2019 (12.72%) to January 2019 (17.24%), which suggests growth in preparation for spawning; decline in the condition index on February 2019 (13.95%) is attributed to stress due to spawning season. Condition index peaked in March 2019 (17.44%). Results verified that Leyte Bay has appropriate environmental condition suitable for mussel growth. This study may help our local farmers in terms of proper timing of harvesting and attain a more sustainable mussel culture.